Strategic Capabilities and Its Influence on Small and Medium Enterprises Competitive Performance: The Moderating Role of Dynamic Business Environment - Idolor, Elohor Katherine; Adebisi, Sunday Abayomi; Ifere, Simeon, E. (Business and Entrepreneurial Review, 2023)
Abstract At present majority of firms are operating in an evolving and vibrant environment that threatens their survival in the competitive economies. Also the increasing globalisation of business is being accelerated around the world and succeeding within a highly competitive environment calls for aggressive deployment of firms’ business strategy, core competences, resources allocation and utilisation that result to the firm attaining a comparative advantage over its competitors. However the erratic market and increasing competitions from multinational firms offering similar homogenous products is challenging to SMEs operation. Similarly, the market landscape for business operating locally or globally is relatively a complex one and a highly competitive avenue for SMEs to operate efficiently, because SMEs do have fewer resources and capabilities to deal with the market challenges as they arise. The study aimed at empirically analysing the influence of strategic capabilities on SMEs performance by developing a framework that takes into consideration the moderating effect of the business environment. The identified framework was validated from the empirical data gathered through the explorative questionnaire survey of 288 managers of manufacturing SMEs in Lagos State, Nigeria. The findings suggest that SMEs firms are able to address business environment challenges when they understand and explore the relevant strategic capabilities that can result to business growth and expansions. As a survival measure entrepreneurs and SMEs owners must be able to identify the pre-eminent capabilities i.e. resources, skills, competencies, knowledge that can be exercised operationally and utilised to achieve competitiveness and sustainability in the long run.